CT examination of the manipulation system in the giant panda (Ailuropoda melanoleuca) - ENDO, HIDEKI (1999)

(untitled)
The manipulation mechanism of the giant panda (Ailuropida melanoleuca) was examined by means of CT (computed tomography) and 3-dimensional (3-D) Volume Rendering techniques. In the 3-D images of the giant panda hand, not only the bones but also the muscular system was visualised. Sections of the articulated skeleton were obtained. It was demonstrated that the hand of the panda is equipped with separately moulded manipulation units as follows: (1) the radial sesamoid (RS), the radial carpal, and the first metacarpal (R–R–M) complex; and (2) the accessory carpal (AC) and the ulnar (A–U) complex. When the giant panda grasps anything, the R–R–M complex strongly flexes at the wrist joint, the RS becomes parallel with the AC, and the phalanges bend and hold the object. It is shown that the well-developed opponens pollicis and abductor pollicis brevis muscles envelop and fix the objects between the R–R–M complex and the phalanges during grasping.